A family of secreted pathogenesis‐related proteins in Candida albicans. Issue 1 (10th December 2012) - Röhm, M.; Lindemann, E.; Hiller, E.; Ermert, D.; Lemuth, K.; Trkulja, D.; Sogukpinar, O.; Brunner, H.; Rupp, S.; Urban, C. F.; Sohn, K.
Summary Analysing culture supernatants of yeast and hyphal cells of Candida albicans, we found two close homologues of pathogenesis‐related (PR‐) 1 proteins, Rbe1p and Rbt4p, in the secretome. Due to sequence homology, three additional, yet not characterized open reading frames, ORF19.6200, ORF19.2787 and ORF19.2336, together with RBE1 and RBT4 were assigned to a novel family of CaPRY proteins. In a Δrbe1/Δrbt4 deletion strain, genome‐wide transcriptional analysis revealed differential transcription of only a limited set of genes implicated in virulence and oxidative stress response. Single deletion of RBE1 or RBT4 in a clinical C. albicans isolate resulted in a moderate but significant attenuation in virulence in a mouse model for disseminated candidiasis. However, a synergistic effect was observed in a Δrbe1/Δrbt4 double deletion strain, where virulence was strongly affected. Remarkably, transcription of RBT4 and RBE1 was each upregulated in blastospores of Δrbe1 or hyphae of Δrbt4 deletion strains respectively, indicating functional complementation thereby compensating a potential virulence defect in the single deletion strains. Furthermore, the double deletion strain showed increased sensitivity to attack by polymorphonuclear leucocytes. Therefore, the crucial contribution of both C. albicans pathogenesis‐related proteins to virulence might be vested in protection against phagocyte attack.